2002
DOI: 10.1007/s00223-001-2090-y
|View full text |Cite
|
Sign up to set email alerts
|

A Comparison of Alfacalcidol and Menatetrenone for the Treatment of Bone Loss in an Ovariectomized Rat Model of Osteoporosis

Abstract: We conducted this study to evaluate the characteristic effects of alfacalcidol (ALF) and menatetrenone (VK) in preventing bone loss using an ovariectomized rat model of osteoporosis. Bilateral ovariectomy (OVX) or sham operation was performed on 10-month-old female Wistar rats. OVX caused a significant decrease in the bone mass and the mechanical strength of the lumbar vertebra as well as the femur 6 months after surgery. VK treatment (30 mg/kg, food intake) required a 6-month period to prevent the bone loss i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
42
1
1

Year Published

2005
2005
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 69 publications
(49 citation statements)
references
References 0 publications
3
42
1
1
Order By: Relevance
“…The beneficial effects of ALF on cancellous bone mass and structure in ovariectomized rats has been well documented; ALF increased not only cancellous bone mass and the Tb Th, but also three-dimensional cancellous bone mass by reinforcing the interconnectivities and structures of the trabeculae (3,23). The beneficial effect of ALF on cancellous bone mass in ovariectomized rats was primarily due to its suppression of bone resorption and maintenance or even stimulation of bone formation (3).…”
Section: Discussionmentioning
confidence: 99%
“…The beneficial effects of ALF on cancellous bone mass and structure in ovariectomized rats has been well documented; ALF increased not only cancellous bone mass and the Tb Th, but also three-dimensional cancellous bone mass by reinforcing the interconnectivities and structures of the trabeculae (3,23). The beneficial effect of ALF on cancellous bone mass in ovariectomized rats was primarily due to its suppression of bone resorption and maintenance or even stimulation of bone formation (3).…”
Section: Discussionmentioning
confidence: 99%
“…Urine calcium was also observed to be significantly higher in the unsupplemented Ovx group. Contrary to Shiraishi et al, [17] who reported a decline in the mean calcium/ creatinine ratio in the Ovx animals, there was a decrease in the alendronate supplemented group, but an increase in the unsupplemented group in our study. Previously, urinary calcium was reported to decrease with varying doses of bisphosphonates; however, this decline appears not to be dose-dependent.…”
Section: Discussioncontrasting
confidence: 99%
“…Similar positive effects of alendronate have been also reported in the literature. [9][10][11][12][13][14][15][16][17] In addition, plasma calcium levels decreased in the Ovx group, compared to the Shm and alendronate groups with no difference between the Shm and alendronate groups. Iwamoto et al [14] reported decreased plasma osteocalcin and urine deoxypyridinoline levels with increased plasma calcium levels in the Ovx rats.…”
Section: Discussionmentioning
confidence: 90%
“…Consistently, previous studies indicated that VK improves bone strength without necessarily increasing BMD (33). These effects of VK are considered to be due to the increase of active (carboxylated) OC and lysyl oxidase-mediated enzymatic cross-linking of collagen, thereby improving bone strength (elasticity and toughness) without significantly affecting BMD (34)(35)(36). Notably, the combination of VK and TPTD increased the BMD compared to VK alone.…”
Section: Discussionsupporting
confidence: 72%